Reasons for non-compliance with quality standards at primary healthcare clinics in Ekurhuleni, South Africa - Lebuile J. Mogakwe; Hafisa Ally; Nomasonto B.D. Magobe (African Journal of Primary Health Care & Family Medicine, 2020)
Background: The South African Minister of Health stated that compliance with quality standards in health services is non-negotiable as it is fundamental in improving South Africa’s current poor health outcomes, restoring patient and staff confidence in the public healthcare system, achieving widespread sustainable development and providing basic quality healthcare in South Africa. Non-compliance with quality standards, as evidenced by increased quality-related queries from the community, prompted the researcher to explore and describe the reasons for such at primary healthcare clinics in Ekurhuleni. Aim: This study sought to explore and describe the reasons for non-compliance with quality standards at the primary healthcare in Ekurhuleni in order to propose recommendations to facilitate compliance with quality standards. Setting: The study was conducted at primary healthcare clinics in Ekurhuleni, one of the metropolitan districts, situated in an area east of the Gauteng province. Methods: A qualitative, exploratory, descriptive and contextual research design was used for this study. Participants were purposefully selected from the population and consisted of individuals who willingly consented to participate. Twelve semi-structured individual interviews were conducted. Results: The study findings revealed challenges with management practices, for example, non-involvement in decision-making, lack of support and poor internal communication practices. In addition, challenges with human, material and financial resources were stated as reasons for non-compliance with quality standards. Conclusion: Recommendations to facilitate compliance with quality standards were described, which included implementation of effective management practices and allocation of adequate healthcare resources required to facilitate such compliance.